Islands of ice on Mars and Pluto - Sori, Michael M.; Bapst, Jonathan; Becerra, Patricio; Byrne, Shane (Journal of Geophysical Research: Planets, 2019)
Ice sheets, such as the polar layered deposits (PLDs) of Mars, are of great interest as records of past climate. Smaller outlier ice deposits near the north and south PLDs are likely more sensitive to climate changes and thus may hold information about more recent climate history. However, the southern outlier deposits have largely remained unmapped and unanalyzed. Here, we identify 31 deposits near, but separated from, Mars's south PLDs, all of which are located within impact craters >15 km in diameter. On the basis of morphology, radar analysis, physical similarity to portions of the PLD margin, and overall similarity to previously described deposits in Mars's north polar region, we conclude that these deposits are primarily composed of water ice. An additional 66 craters contain smaller depositional features, some of which may be remnant ice deposits. The 31 outlier ice deposits represent a previously unquantiﬁed inventory of water on Mars, with a total volume between 15,000 and 38,000 km3. In addition, we identify ﬁve analogous outlier nitrogen ice deposits located within impact craters near Sputnik Planitia, the large nitrogen ice sheet on Pluto. Although important differences exist between Mars and Pluto, broad physical similarities between the two cases suggest that the topography and microclimates of impact craters cause them to be favorable locations for volatile accumulation and/or retention throughout the Solar System.